PENGUATAN KELOMPOK KERJA PEMBANGUNAN DESA (K2PD) TERHADAP PENGELOLAAN SUMBER DAYA ALAM BERPERSPEKTIF GENDER DI KECAMATAN ANGGABERI KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Laxmi . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This study focuses on determining women's access and control in the management of natural resources, describing the independence of women, and knowing the forms of empowerment by the oil palm company to transform functions of forests. The scope of this study is women who joined K2PD in District of Anggaberi, Konawe Regency. This study is a qualitative research by applying the techniques of observation, participation of observation, and deep interview. Determination of informants uses snowballing techniques. To deepen this study, the study also uses literature review and secondary data collection with reference to Spradley. The result of study found that women who joined K2PD have limitations in the management of natural resources after an influx of the oil palm company. However, it was a positive impact for the reduction of unemployment in the village who had worked as an employee of the office or as a field worker. After operating for five years, the oil palm company had not empowering to the community, especially in the rural development working groups and the general public. Social aids provided in the form of the physical facilities. Keywords: strengthening, management, resources, women and K2PD